Measuring knowledge and action changes in the light of urban climate resilience. (April 2021) - Wilden, Daniela; Feldmeyer, Daniel
Abstract: Climate resilience has gained an essential role in research as well as in international policies. An increasing number of cities are adapting to climate change to enhance their climate resilience. Given the complexity of urban systems in combination with the acceleration of climate and social change, it is challenging to measure the success of resilience-rising activities. To manage and accelerate the learning process and the transformation process, monitoring and evaluation of implemented adaptation measures are crucial. Most of the currently used indicator sets are dealing with system-focused changes. However, actor-focused changes are less addressed in holistic indicator sets, even if individual agency assumes an important role in the transformation process. This research was intended to design a framework for individual climate resilience agency and operationalise it in a composite indicator set. The indicator set is implemented in a survey with 14 research projects in Germany. Finally, the indicator set is verified using statistical and empirical validation. The study presents an applicable indicator set, which reveals more in-depth insights into the individual climate resilience agency and changes within adaptation measurements. Further, the set can be applied in both one-time assessments and repetitive measurement. Therefore, the tool can be implemented as a monitoring tool, as well as a formative evaluation tool, in the climate resilience adaptation context.